Morpho-Physiological Traits and Functional Markers Based Molecular Dissection of Heat-Tolerance in Urdbean - Sen Gupta, Debjyoti; Basu, Partha S.; Souframanien, J.; Kumar, Jitendra; Dhanasekar, P.; Gupta, Sanjeev; Pandiyan, Muthaiyan; Geetha, S.; Shanthi, P.; Kumar, Vaibhav; Pratap Singh, Narendra (Frontiers in Plant Science, 2021)
Urdbean (Vigna mungo L. Hepper) is one of the important pulse crops. Its cultivation is not so popular during summer seasons because this crop is unable to withstand excessive heat stress beside lack of humidity in the atmosphere. Therefore, a panel of 97 urdbean diverse genotypes was assessed for yield under stress and non- stress conditions with an aim to identify heat tolerant genotypes. This study identified eight highly heat tolerant and thirty-five highly heat sensitive genotypes based on heat susceptibility index. Further, physiological and biochemical traits based characterization of a group of six highly heat sensitive and seven highly heat tolerant urdbean genotypes showed genotypic variability for leaf nitrogen balance index (NBI), chlorophyll (SPAD), epidermal flavnols and anthocyanin contents under 42/25º C max/min temperature. Our results showed higher membrane stability index among heat tolerant genotypes compared to sensitive genotypes. Significant differences among genotypes for ETR at different levels of PAR irradiances and PAR ×genotypes interactions indicated high photosynthetic ability of few genotypes under heat stress. Further, most highly sensitive genotype PKGU-1 showed decrease in different fluorescence parameters indicating distortion of PS II. Consequently, reduction in the quantum yield of PS II was observed in sensitive one as compared to tolerant genotype. Fluorescence kinetics showed the delayed and fast quenching of Fm in highly heat sensitive (PKGU 1) and tolerant (UPU 85-86) genotypes, respectively. Moreover, tolerant genotype (UPU 85-86) had high antioxidant activities explaining their role for scavenging superoxide radicals (ROS) protecting delicate membranes from oxidative damage. Molecular characterization further pinpointed genetic differences between heat tolerant (UPU 85-86) and heat sensitive genotype (PKGU 1). These findings will contribute to the breeding towards the development of heat tolerant cultivars in urdbean.